Intralesional Avirulent Bacillus Calmette-Guérin Injection as a Promising Method for the Treatment of Tuberculosis Verrucosa Cutis - Özgür Gündüz; Gülşah Koçak; Birgül Kaçmaz; Tuba Devrim; Hülya Şimşek (Karger Publishers, 2022)
Cutaneous involvement is a relatively uncommon manifestation of tuberculosis (TB), particularly outside the endemic regions. Cutaneous TB manifests itself in various clinical forms, depending on the host's immune status and mode of transmission. Nonetheless, the same treatment regimen is recommended for every subtype. Tuberculosis verrucosa cutis (TBVC) is a specific subgroup in which the affected persons are usually healthy adults who are vaccinated or exposed to mycobacteria during their occupational activities. These patients have the ability to launch a strong cellular immune reaction against mycobacteria. In this article, we present an elderly patient with a 4-year history of TBVC who was treated with intralesional injection of avirulent Bacillus Calmette-Guérin (BCG) and report our clinical observation on the inflammatory and healing process of the patient's lesion following the intralesional BCG injection.